The Application of the CRISPR-Cas System in Antibiotic Resistance - Tao S; Chen H; Li N; Liang W (Infection and Drug Resistance, 2022)
Shuan Tao,1,2 Huimin Chen,1 Na Li,3 Wei Liang2 1School of Medical, Jiangsu University, Zhenjiang, Jiangsu Province, 212013, People’s Republic of China; 2Lianyungang Clinical College of Jiangsu University, Lianyungang, Jiangsu Province, 222023, People’s Republic of China; 3Bengbu Medical College, Bengbu, Anhui Province, 233030, People’s Republic of ChinaCorrespondence: Wei Liang, Lianyungang Clinical College of Jiangsu University, No. 161. Xingfu Road, Haizhou District, Lianyungang, Jiangsu Province, 222023, People’s Republic of China, Tel/Fax +86-51885213100 ; Tel/Fax +86 15351883016, Email hslwys@163.comAbstract: The emergence and global epidemic of antimicrobial resistance (AMR) poses a serious threat to global public health in recent years. AMR genes are shared between bacterial pathogens mainly via horizontal gene transfer (HGT) on mobile genetic elements (MGEs), thereby accelerating the spread of antimicrobial resistance (AMR) and increasing the burden of drug resistance. There is an urgent need to develop new strategies to control bacterial infections and the spread of antimicrobial resistance. The clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated proteins (Cas) are an RNA-guided adaptive immune system in prokaryotes that recognizes and defends against invasive genetic elements such as phages and plasmids. Because of its specifically target and cleave DNA sequences encoding antibiotic resistance genes, CRISPR/Cas system has been developed into a new gene-editing tool for the prevention and control of bacterial drug resistance. CRISPR-Cas plays a potentially important role in controlling horizontal gene transfer and limiting the spread of antibiotic resistance. In this review, we will introduce the structure and working mechanism of CRISPR-Cas systems, followed by delivery strategies, and then focus on the relationship between antimicrobial resistance and CRISPR-Cas. Moreover, the challenges and prospects of this research field are discussed, thereby providing a reference for the prevention and control of the spread of antibiotic resistance.Keywords: antibiotic resistance, CRISPR-Cas, horizontal gene transfer